Ferroptosis Detection: From Approaches to Applications - Zeng, Fantian; Nijiati, Sureya; Tang, Longguang; Ye, Jinmin; Zhou, Zijian; Chen, Xiaoyuan (Angewandte Chemie International Edition, 2023)
Understanding the intricate molecular machinery that governs ferroptosis and leveraging this accumulating knowledge could facilitate disease prevention, diagnosis, treatment, and prognosis. Emerging approaches for the in situ detection of the major regulators and biological events across cellular, tissue, and in living subjects provide a multiscale perspective for studying ferroptosis. Furthermore, advanced applications that integrate ferroptosis detection and the latest technologies hold tremendous promise in ferroptosis research. In this review, we first briefly summarize the mechanisms and key regulators underlying ferroptosis. Ferroptosis detection approaches are then presented to delineate their design, mechanisms of action, and applications. Special interest is placed on advanced ferroptosis applications that integrate multifunctional platforms. Finally, we discuss the prospects and challenges of ferroptosis detection approaches and applications, with the aim of providing a roadmap for the theranostic development of a broad range of ferroptosis‐related diseases. We systematically summarize the ferroptosis detection approaches for subcellular organelles, biological events, and chemical markers, providing a multi‐scale perspective on the regulation of the molecular machinery of ferroptosis. Moreover, we highlight the potential of advanced applications that integrate ferroptosis detection techniques with multifunctional platforms. The development of these applications holds great promise in promoting the transition of ferroptosis research from bench to bedside.